An Impressionist-Existentialist Study of "Station" by Tahereh Alavi and "the Only One" and "Meet" by Abdul Hamid Al-Gharbawi - Narjes Tohidifar; Reza Nazemian (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Impressionism and existentialism are both schools of thought that consider the human and his/her existence as the center of the universe. In Impressionism, it is the individual who, as the creator and recorder of a moment, immortalizes it because he/ she is the one who experiences and then creates and represents that moment. Existentialism also maintains that philosophical thinking begins with the subject of human, not merely subjective thinking, and that life is meaningless unless one gives it meaning. The present study seeks to answer the question: why and how did both Alavi and Al-Gharbawi use a combination of impressionist-existentialist approach in their works: "The Station", and "the Only One" and "Meet" respectively? The importance of the research lies in its examination of a gap in criticism; it seems that interdisciplinary approach to criticism can offer a more comprehensive  study of the text. For this purpose, the current research makes an attempt to offer a new form of reading the text by combining the two schools of impressionism and existentialism. To do this, three short and very short stories have been selected, one from the contemporary Persian literature and the other two from the contemporary Arabic literature. This research is of analytical-descriptive nature. The results indicate that Alavi and Al-Gharbawi try to express the loneliness and emptiness of the life of the contemporary man. Although Alavi tends to associate this loneliness with gender criticism, both authors have been able to draw on impressionism and existentialism to reach an epiphanic moment of recognition and understand the feeling of philosophical absurdity.